2019
DOI: 10.1186/s12955-019-1153-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in pregnancy with uterine fibroid: a cross-sectional study in China

Abstract: Background Uterine fibroids (UFs) are the most common benign tumors in women. They are likely to cause numerous clinical symptoms, such as pain, menorrhagia, and other obstetric complications in pregnant women. This study aimed to determine the health-related quality of life (HRQoL) during pregnancy with uterine fibroids (UF), thus providing a utility-based case value in pregnant women with UF and understanding of whether HRQoL is associated with clinical outcomes in pregnant women with UFs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…In addition to this, factors that may affect QoL have also been studied. It was appropriate to use a generalised questionnaire to determine the subject's health-related quality of life (HRQoL) values [33][34][35][36], given that most pregnant women do not have a fatal illness [37]. As one of the most common means for assessing the overall health of the body, EQ-5D is a powerful generic tool, particularly in regards to evaluating symptoms of pain and anxiety/depression [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, factors that may affect QoL have also been studied. It was appropriate to use a generalised questionnaire to determine the subject's health-related quality of life (HRQoL) values [33][34][35][36], given that most pregnant women do not have a fatal illness [37]. As one of the most common means for assessing the overall health of the body, EQ-5D is a powerful generic tool, particularly in regards to evaluating symptoms of pain and anxiety/depression [38].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the research findings of other previous studies, we found that pregnant women exposed to FHS and SHS have a similar, and sometimes even much lower HRQoL than those suffered from physiological diseases, such as gestational diabetes mellitus and uterine fibroid. [29,50] Although electronic cigarettes has been considered as a safer way than smoking tobacco among people recent years, [51] recent studies have stated that e-cigarette products still can cause varying degree of lung damage and chronic respiratory symptoms and both DNA strand breaks and cell death; [52][53][54] Thus, the…”
Section: Discussionmentioning
confidence: 99%
“…Through the EQ-5D indicator value calculator, the values of different levels for each question are arranged and can be calculated as a single EQ-5Dindicator value (such as 12121) to generate the final HRQoL value. In this manner, 1 indicating the best health state while 0 represents death [28,29,31]. Range of EQ-index value is in the interval of -0.224 to 0, and these negative values represent their overall health states (both physical and mental state) are worse than death [31].…”
mentioning
confidence: 99%
“…EQ-5D-5L consists of the EuroQoL Fivedimension Questionnaire (EQ-5D) and EuroQol group's visual analog scale (EQ-VAS), which is an instrumental questionnaire developed in Europe was used to evaluate the general HRQoL of the people [27,28]. Previous study has proved that EQ-5D-5L can effectively measure health-related quality of life in pregnant women in the population [29]. The Chinese version of the EQ-5D-5L has been proved to be valid and effective that is commonly used to measure HRQoL [30][31][32].…”
Section: Study Design and Populationmentioning
confidence: 99%